2011
DOI: 10.1007/s00436-011-2628-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parasitological and immunological parameters of Leishmania chagasi infection in BALB/c mice using different doses and routes of inoculation of parasites

Abstract: Experimental vaccines to protect against visceral leishmaniasis (VL) have been developed by using BALB/c mice infected with a large (10⁷ to 10⁸) inoculum of parasites. Remarkably, prior literature has reported that the poor protection observed is mainly due to the high susceptibility of this strain. To determine factors inherent to mice that might abrogate vaccine-induced efficacy, the present research sought to investigate the impact of the administration of different infective inoculums of Leishmania chagasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…Because the spleen is considered a systemic organ for the transit and homing of T cells in mammal hosts, and because it is an important site of infection for Leishmania spp. parasites (64) , one may speculate that the greater presence of the NQC-AmpB nanoparticles in the spleen might be adequate for the treatment of leishmaniasis. Remarkably, ChS has been detected in many tissues and host cells (65) , and it has been reported to biologically interact with important molecules and to regulate their functions.…”
Section: Optimized Nanoparticle Delivery Systems For Ampb Based On Chmentioning
confidence: 99%
“…Because the spleen is considered a systemic organ for the transit and homing of T cells in mammal hosts, and because it is an important site of infection for Leishmania spp. parasites (64) , one may speculate that the greater presence of the NQC-AmpB nanoparticles in the spleen might be adequate for the treatment of leishmaniasis. Remarkably, ChS has been detected in many tissues and host cells (65) , and it has been reported to biologically interact with important molecules and to regulate their functions.…”
Section: Optimized Nanoparticle Delivery Systems For Ampb Based On Chmentioning
confidence: 99%
“…65 The present study showed that BALB/c mice, when infected with a highly infective inoculum, developed an exponential parasite burden in organs such as dLN, footpad, spleen, and liver, which suggests a chronic infection in the animals, and makes it very difficult to control the replication of parasites. 66 In this context, one could speculate that even using a very effective treatment regimen, the infected animals would not be able to clear all parasites in the different organs. In this light, the NQC-AmpB nanoparticles could be considered as effective therapeutic agents; once the results obtained in the animals treated with this product were compared with the data shown in the free-AmpB-treated group, although not all parasites had been eliminated.…”
mentioning
confidence: 99%
“…The liver appears to serve as an indicator of the multiplication of parasites in the acute phase of the infection (Oliveira et al, 2012), and granuloma formation has been associated with a selflimiting hepatic infection, whereas these same granuloma fail to take form in the spleen, where parasites more commonly persist (Murray, 2001). Together, these observations suggest a causal association between granuloma formation and host resistance to visceralizing species of Leishmania spp., such as L. infantum (Moore et al, 2013).…”
Section: Discussionmentioning
confidence: 97%